DESAIN ULANG KEMASAN PRODUK MAKANAN TRADISIONAL JENANG KHAS KABUPATEB KUDUS UNTUK MENINGKATKAN DAYA BELI MASYRAKAT - Ayyub Hamdanu Budi Nurmana Mulyana Slamet; Mars Caroline Wibowo (Pixel :Jurnal Ilmiah Komputer Grafis, 2021)
Packaging is one part of the product as a whole. Packaging must be able to attract the attention of consumers. Getting the attention of consumers is very important, because if a product does not get the attention of consumers (consumer attention), then consumers will not have a picture of the product (Hine, 1995). Packaging can give an initial picture of a product, both in terms of quality and value offered. “Jenang Kudus” is a type of traditional food originating from the city of Kudus. At first it was produced in a home industry since about a century ago. Initiated by mothers as a supporter of family income, and marketed directly to local consumers in traditional markets. Because the development of this business in the future is considered quite prospective for the Kudus community, the Kudus Regency Government makes the Jenang Kudus product as the mainstay product of the Kudus Regency. Based on some of the explanations above, there are several weaknesses in the packaging design of CV jenang products. Sinar Aisyah Kudus which can cause delays in the marketing process of its products due to unattractive packaging designs. This causes a desire to increase the competitiveness of jenang sales with other companies through attractive and varied packaging designs. Due to some of these things, raises the desire of CV. Hj Siti Aisyah to redesign the product packaging according to the type of jenang product, type of taste, quantity of contents, without leaving the characteristics of the previous design.